Graphic exploration, learning, invention and modelling: information design as a process for interview analysis - Carvalho, Ricardo Artur; Oliveira da Silva Sidaoli, Leonardo; Jardim Batista, Cristina (InfoDesign, 2023)
This article explores the use of graphical visual language in research processes as a form of investigation and learning. Based on the case of a master’s thesis, the authors examine the process of graphic exploration and how it contributed to the results of the analysis of ten interviews. The use of different graphic resources and how they served to represent and translate elements present in the interviewees’ speeches, to organise, identify the recurring themes and, subsequently, analyse them is observed. It was found that the process of exploring and analysing the interviews was enhanced by the design process, which experimented with different configurations of organisation and categorisation were experimented, articulating concepts and forms throughout the process.